Stress corrosion testing of roof bolt grade 60 steel in simulated underground coal mine atmosphere. Issue 4 (2nd October 2019) - Bylapudi, Gopi; Spearing, A. J. S. (Sam); Mondal, Kanchan; Bhagwat, Anand
ABSTRACT: Corrosion of roof bolts in underground mine environments could have an adverse impact on ground control, which is directly related to workforce safety. Past studies state that stress corrosion cracking (SCC) of roof bolts is a significant problem in underground coal mines, resulting in premature bolt failures. However, it has not been seriously studied in U.S. underground coal mines. As a preliminary study, the most common roof bolt material used in U.S. mines, ASTM A 615 Grade 60 steel, was studied under stress corrosion conditions. ASTM G30 standard was applied to achieve this and tested in the simulated coal mine conditions. SCC was observed on samples that were tested for 180 days. Chloride SCC (ClSCC) was found to be the corrosion mechanism resulting in cracks from the EDS data. This paper mainly discusses the test protocol, shortcomings of this preliminary testing and makes recommendations based on the observations and results.